Penerapan Metode Bermain Peran untuk Meningkatkan Keterampilan Berbicara Siswa Kelas IV pada Pembelajaran Bahasa Indonesia di Sekolah Dasar Negeri 67 Tanjung Gedang Bangko - Riendi Yani; Minnah El Widdah (Jurnal Pendidikan, Bahasa dan Budaya, 2025)
In order to improve the quality of education, speaking skills are one of the important aspects that students need to have. However, in reality the speaking skills of class IV students at State Elementary School 67 are still low. Therefore, this research aims to improve students' speaking skills through the application of role-playing methods. This research uses the Kemmis and McTaggart model which consists of four stages, namely planning, action, observation and reflection. In this way, it is hoped that students' speaking skills can improve and become more effective in communicating. Based on the results of observing teacher activities in cycle I, results were obtained with a percentage of 75%, then in cycle II teacher activity increased to 92% with very good qualifications. Meanwhile, the results of observing student activities in cycle I obtained a result of 73.73% and increased in cycle II to 88% with very good qualifications. Based on these data, it shows that there has been an increase in teacher and student activity in implementing role-playing methods in the learning process. Thus it can be concluded that the application of the role playing method is able to improve students' speaking skills in learning Indonesian for class IV students at State Elementary School 67.